Ischemic stroke in 455 COVID-19 patients - Finsterer, Josef; Scorza, Fulvio Alexandre; Scorza, Carla Alessandra; Fiorini, Ana Claudia (Clinics, 2022)
There is increasing evidence that COVID-19 can be associated with ischemic stroke (COVID-stroke). The frequency and pathogenesis of COVID-stroke, however, remains largely unknown. This narrative review aimed at summarizing and discussing current knowledge about frequency and pathogenesis of COVID-stroke in 455 patients collected from the literature. COVID-stroke occurs in all age groups and predominantly in males. The anterior circulation is more frequently affected than the posterior circulation. COVID-stroke is most frequently embolic. The severity of COVID-stroke ranges from NIHSS 3 to 32. Cardiovascular risk factors are highly prevalent in patients with COVID-stroke. COVID-stroke occurs simultaneously with the onset of pulmonary manifestations or up to 40 days later. Clinical manifestations of COVID-19 are most frequently mild or even absent. The majority of patients with COVID-stroke achieve complete or partial recovery, but in one-quarter of patients, the outcome is fatal. In conclusion, the frequency of ischemic stroke has not increased since the outbreak of the SARS-CoV-2 pandemic. COVID-stroke predominantly affects males and the anterior circulation. COVID-stroke is multifactorial but predominantly embolic and more frequently attributable to cardiovascular risk factors than to coagulopathy.